2015
DOI: 10.1016/j.envres.2015.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Tea consumption in pregnancy as a predictor of pesticide exposure and adverse birth outcomes: The MIREC Study

Abstract: Pesticide concentrations did not differ by tea intake. Further, tea intake in the first trimester was not associated with adverse birth outcomes. In this study population, there was no evidence for concern about tea intake being a source of the OP or OC pesticide metabolites measured or adversely affecting birth outcomes; however, tea intake was lower than national Canadian data for women of reproductive age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
(25 reference statements)
0
8
1
Order By: Relevance
“…Regarding the comparison with our study, the metabolite concentrations observed in our study population were lower than those in the women from Norway, Netherlands, and USA. TCPy, DMTP, DEP, and DETP concentrations in our cohort were much lower than those reported for pregnant women from Shanghai (China) [14], Cincinnati (USA) [21], Mexico DF [35], and Canada [22, 24]. Similar concentrations of DEP and TCPy to those of our study were found in the Caribbean Islands [36] and Puerto Rico [23] studies, respectively, although the detection frequencies in our study were lower.…”
Section: Discussioncontrasting
confidence: 64%
“…Regarding the comparison with our study, the metabolite concentrations observed in our study population were lower than those in the women from Norway, Netherlands, and USA. TCPy, DMTP, DEP, and DETP concentrations in our cohort were much lower than those reported for pregnant women from Shanghai (China) [14], Cincinnati (USA) [21], Mexico DF [35], and Canada [22, 24]. Similar concentrations of DEP and TCPy to those of our study were found in the Caribbean Islands [36] and Puerto Rico [23] studies, respectively, although the detection frequencies in our study were lower.…”
Section: Discussioncontrasting
confidence: 64%
“…Sample size ranged from 27 to 500 women in interventional studies, 187 to 860,215 women in observational studies, and one to five women in case reports. Seven studies collected data during the first trimester of pregnancy; 71,82,85,88,96,105,107 10 during the second trimester; 41,58,67,81,83,84,87,89,101,108 12 during the third trimester; 38,62,64,80,91,92,100,102,103,106,109,110 five throughout pregnancy; 69,70,75,90,95 five around the time of labor (a few hours before or after delivery); 37,59–61,77 nine throughout pregnancy and the postnatal period; 14,31,39,7274,78,79,111 three during the third trimester and the postnatal period; 40,112,113 20 during the postnatal period only; 24,34,56,63,65,66,68,76,86,94,9799,104,114119 and two did not specify the precise point during pregnancy of data collection. 57,93…”
Section: Resultsmentioning
confidence: 99%
“…The methods used to identify adverse events and herb–drug interactions were clinical examination; 3741,56,57,59,60,63,70,81,82,105,107112,114119 patient interviews; 61,65,78,86,93,100,106 patient questionnaires; 24,31,34,7274,76,85,90,94,95,9799 diary cards; 62,66,68 laboratory or imaging studies (ie, hematologic and biochemical results, ultrasonography); 71,79,102,120 and review of medical records. 14,64,65,75,77,88,91,92,96,100,113 Eleven studies did not mention how adverse events or herb–drug interactions were identified.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drinking non-herbal tea was one of the only significant dietary predictors found to be positively associated with 3-PBA biomarker concentrations in two models (Models A and C). Previous studies suggest that residues of pesticides can persist in samples of teas [ 75 , 76 , 77 ]. We also found that eating any organic food predicted lower concentrations of IMPy and 3-PBA, metabolites of diazinon, and pyrethroids such as permethrin.…”
Section: Discussionmentioning
confidence: 99%